Echocardiographic changes in the shape and size of the aortic cusps in dogs with confirmed systemic hypertension. Issue 6 (15th June 2021) - Holland, Merrilee; Hofmeister, Erik; Hudson, Judith
Abstract: Systemic hypertension (SH) in dogs typically occurs secondary to renal disease, diabetes mellitus, hyperadrenocorticism, malignant adrenal tumors, or various medications. Echocardiography performed on people with SH has shown asymmetric dilation of the sinuses at the level of the aortic valves, previously undescribed in canine patients. The objective of this retrospective case‐control study was to determine if there was a difference in size and shape of the aortic cusps at the level of the sinus of Valsalva in dogs with SH compared to dogs with normal blood pressure. We reviewed echocardiographic findings in 74 dogs with SH and 37 dogs with normal blood pressure (NBP), defined as less than 150 mmHg. Systemic hypertension was classified as mild (150‐159 mm Hg), moderate (160‐179 mm Hg), or severe (greater than 180 mm Hg). There was a significant difference ( P < .001) in the mean size of the aorta cusps at the level of the sinuses in 67 of 74 dogs with SH and none of 37 dogs with NBP. Of the 74 dogs with SH, 70 had left ventricular hypertrophy (18 asymmetric, 15 concentric, and 37 eccentric). Additionally, there was aortic root dilatation in 15 dogs, aortic insufficiency in 21, mitral regurgitation in 50, and left atrial enlargement in 71. The standard deviation of the three cusp measurements between the dogs with SH and dogs with NBP had a sensitivity of 92% and specificity of 97% for diagnosis of SH. Asymmetric size of the aortic cusps on echocardiography is therefore a reliable indicator of SH in dogs.